Social organizations and the authoritarian state in China - Hildebrandt, Timothy, 1978- (Cambridge ; New York : Cambridge University Press, 2013)
"Offers a groundbreaking comparative analysis of the emergence of NGOs across China in three different issue areas: environmental protection, HIV/AIDS prevention, and gay and lesbian rights"--
"For all of the attention that has been paid to social organizations - and the research conducted on them - our understanding has still been significantly limited by the persistent assumptions surrounding the effect of NGO emergence, the internal orientation of the organizations, and the relations they have with states. In the West, we have been conditioned to see the rise of non-governmental organizations (NGOs) in fairly stark, axiomatic terms. The presence of NGOs is thought to be an important indicator of civil society development. And with a robust civil society, political change is thought to soon follow. Part of the logic at work is that NGOs and civil society are frequently seen to hold governments accountable. In authoritarian contexts, where the government is not accountable to its citizenry (at least in an electoral sense), we presume these accountability-seeking organizations to be oppositional to the state. Any reasonable observer would then assume, given their druthers, an authoritarian government would not allow such oppositional groups to exist at all. Perhaps then it makes sense to first assume that NGOs would not exist in a place like China at all. And to the extent that they do appear in the country, we might best assume these organizations to not be authentic 'real' NGOs. This would, of course, be one way of explaining why the political change that many expect to come from the emergence of NGOs has not occurred in China. But it would not be a satisfying explanation"--
Self-limiting organizations and codependent state-society relations : environmental, HIV/AIDS, and gay and lesbian NGOs in China -- Political opportunities, by accident and design -- Central policies, local priorities : regional variation of the political opportunity structure -- Proximate solutions to insoluble problems : adaption to the political opportunity structure -- More money, more problems : struggling with economic opportunities -- Forever the twain shall meet : economic and political opportunities converge -- Strong individual relationships, weak institutional ties : the double-edged pursuit of personal opportunities -- Social organizations and the future of Chinese civil society.
Includes bibliographical references (p. 201-212) and index.
Keywords: Non-governmental organizations -- China; Civil society -- China; China -- Social conditions -- 2000-